Queremos hablar por nosotros mismos - Melillán Painemal; Comité Exterior Mapuche (C.E.M.) (Les Cahiers ALHIM)
In this interview, the Mapuche leader fundamentally refers to a balance of three years of the Centros Culturales Mapuches’s activities, Centers funded in 1978. The interviewed outline the paper of the international solidarity and the perspectives of this organization.